2020
DOI: 10.1186/s12905-020-01025-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of snoring and body composition in (peri-post) menopausal women

Abstract: Background: Little attention has been paid to whether snoring frequency is associated with body composition in menopausal women, particularly in China. This study objected to investigate the association between self-reported snoring and body composition in (peri-post) menopausal Chinese women as well as metabolic indicators. Methods: This cross-sectional study enrolled 715 participants aged 40-67 years from the Menopause Clinic in the Shanghai Sixth People's Hospital. Participants were categorized into four su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The 3250 total study participants were divided into the following three groups based on their self-reported snoring frequency ( Figure 1(a) ): regularly snoring group (≥3 nights per week), occasionally snoring group (frequency between that of the regularly snoring group and never snoring group), and never snoring group (<1 night per month) [ 17 ]. In addition, we separated 3250 study participants into obese individuals and normal-weight individuals according to their waist circumference (obesity defined as ≥90 cm for men and ≥85 cm for women) [ 18 ], and each weight group was stratified according to the same three groups mentioned above ( Figure 1(b,c) ).…”
Section: Methodsmentioning
confidence: 99%
“…The 3250 total study participants were divided into the following three groups based on their self-reported snoring frequency ( Figure 1(a) ): regularly snoring group (≥3 nights per week), occasionally snoring group (frequency between that of the regularly snoring group and never snoring group), and never snoring group (<1 night per month) [ 17 ]. In addition, we separated 3250 study participants into obese individuals and normal-weight individuals according to their waist circumference (obesity defined as ≥90 cm for men and ≥85 cm for women) [ 18 ], and each weight group was stratified according to the same three groups mentioned above ( Figure 1(b,c) ).…”
Section: Methodsmentioning
confidence: 99%